(untitled) (Research, Society and Development, 2022)
The present study aimed to investigate the application of periodization by teachers and masters of combat sports modalities. The sample of the type intentional non-probabilistic was composed of 14 teachers end masters the modalities of Jiu-Jitsu, Judô, Kung Fu, Taekwondo, Muay Thai, Kickboxing e Karatê active in the region. To achieve the proposed objectives, the research used a questionnaire, who investigated the physical preparation process, technique, tactic and psychological of athletes. According to the results obtained, we can identify that most coaches has an academic background in Physical Education. Although everyone said do some kind of planning for the season of your athletes, there is a preference for specific knowledge of each modality. We can conclude that the choice and construction of the models training periodization, used by the studied participants, reflects practical knowledge, experiences of the handmade model and empirical knowledge, the coaches being primarily responsible for preparing and planning the training of their athletes. Although they have not cited any literature, when looking at the way they plan the season, we can identify the similarities to predicted configurations by Matveev Classic Model and the Bompa Extended Income State Model.